Factors Related to the Empowerment of Pesantren Community in Control of Covid-19 in Ujong Fatihah, Nagan Raya - Syarifah Nur; Otniel Ketaren; Mido Ester Sitorus (Jurnal Serambi Engineering, 2022)
Covid-19 is a global pandemic that has caused many deaths. Based on data from World Health Organization (WHO) on March 6, 2021, the confirmed cases of covid-19 were 116,647,031, and 2,588,034 deaths have been documented. One of the places that have also been affected by Covid-19 is pesantren (Islamic Boarding Schools). It is undeniable that pesantren is a gathering place for many people, so the transmission of COVID-19 virus spreads more quickly. This study aimed to identify factors related to the empowerment of the pesantren community in the prevention and control of Covid-19 in Ujong Fatihah, Kuala Sub-District, Nagan Raya. This study was a quantitative study using a cross-sectional design with a total number of populations in this study was 210 people. This study was conducted using a purposive sampling technique, where the sample size was determined by the Slovin Formula. Based on the results of the Chi-Square test, it is known that there are four factors related to the empowerment of the pesantren community in the prevention and control of Covid-19 at the Bustanul Jannah Ujong Fatihah Islamic Boarding School, Kuala Sub-District, Nagan Raya, namely knowledge, students’ compliance, communication, and the role of the leader.